2015
DOI: 10.1002/jaba.199
|View full text |Cite
|
Sign up to set email alerts
|

The value of choice as a reinforcer for typically developing children

Abstract: Previous research has shown that providing choices may result in an increase in appropriate behavior and a decrease in inappropriate behavior; however, the process by which choice results in a behavior change is unknown. In the current study, we replicated and extended previous research by determining the prevalence of preference for choice in a large number of children and evaluating whether a history of differential outcomes associated with choice and no choice resulted in changes in preference for those con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…Additionally, for most participants, the child choice was selected more frequently than the experimenter choice. This interpretation is similar to that of Ackerlund Brandt et al ().…”
Section: Resultssupporting
confidence: 92%
“…Additionally, for most participants, the child choice was selected more frequently than the experimenter choice. This interpretation is similar to that of Ackerlund Brandt et al ().…”
Section: Resultssupporting
confidence: 92%
“…By contrast, our procedures involved conducting two assessment probes following every 150 conditioning trials (10 sessions of 15 trials each). Cumulatively, our participants experienced more conditioning trials, but tended to show preference shifts within the first four probe sessions (i.e., following fewer conditioning trials than those of Ackerlund Brandt et al, ). Several of our participants' data displayed trends during our assessment, suggesting that increased conditioning experience strengthened choice or no‐choice preference, but differences in the number of conditioning trials alone could not account for the differences between our data and Ackerlund Brandt et al’s data.…”
Section: Discussionmentioning
confidence: 67%
“…Of the six children in Tiger et al, three demonstrated a choice preference, two were ambivalent, and one demonstrated a no‐choice preference. Of the 11 children in Ackerlund Brandt et al (), six demonstrated a choice preference during baseline and five demonstrated ambivalence; none demonstrated a preference for no‐choice conditions. In our current study, four participants demonstrated a choice preference during baseline and one demonstrated ambivalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have studied the value of choice by measuring preference between conditions that allow choice‐making opportunities to conditions that do not. Humans (e.g., Ackerlund Brandt, Dozier, Foster Juanico, Laudont, & Mick, ; Fisher, Thompson, Piazza, Crosland, & Gotjen, ; Hori & Shimazaki, ; Karsina, Thompson, & Rodriguez, ; Karsina, Thompson, Rodriguez, & Vanselow, ; Rost, Hemmes, & Alvero, ; Schmidt, Hanley, & Layer, ; Suzuki, , ; Tiger, Hanley, & Hernandez, ) and nonhumans (e.g., Catania, ; Catania & Sagvolden, ; Cerutti & Catania, ; Suzuki, ; Voss & Homzie, ) often prefer situations that permit selection among multiple stimuli when the alternative is a forced‐ or restricted‐choice arrangement. From a behavior analytic perspective, it would be unsurprising if subjects preferred making choices because they resulted in a larger magnitude of reinforcement, for example.…”
mentioning
confidence: 99%